Dynamic Mitotic Localization of the Centrosomal Kinases CDK1, Plk, AurK, and Nek2 in Dictyostelium amoebae - Stefan Krüger; Nathalie Pfaff; Ralph Gräf; Irene Meyer (Cells)
The centrosome of the amoebozoan model Dictyostelium discoideum provides the best-established model for an acentriolar centrosome outside the Opisthokonta. Dictyostelium exhibits an unusual centrosome cycle, in which duplication is initiated only at the G2/M transition and occurs entirely during the M phase. Little is known about the role of conserved centrosomal kinases in this process. Therefore, we have generated knock-in strains for Aurora (AurK), CDK1, cyclin B, Nek2, and Plk, replacing the endogenous genes with constructs expressing the respective green fluorescent Neon fusion proteins, driven by the endogenous promoters, and studied their behavior in living cells. Our results show that CDK1 and cyclin B arrive at the centrosome first, already during G2, followed by Plk, Nek2, and AurK. Furthermore, CDK1/cyclin B and AurK were dynamically localized at kinetochores, and AurK in addition at nucleoli. The putative roles of all four kinases in centrosome duplication, mitosis, cytokinesis, and nucleolar dynamics are discussed.